ХАРАКТЕРИСТИКА САМОКОНТРОЛЮ УЧНІВ ЯК КОМПОНЕНТА НАВЧАЛЬНОЇ ДІЯЛЬНОСТІ (Педагогіка вищої та середньої школи, 2022)
The article deals with the characteristic of the self-control ofpupils as a component of their instructional and cognitive activity, there are represented the kinds and the structural links of instructional self-control.